The Application of Income Tax Incentives In Accordance With The Minister of Finance Regulation (Pmk) No.44/Pmk.03/2020 At Educational Institutions PT. Yureka Education Copyright - Adinda Dwi Cahyakusuma; Ahmad Yani; Rike Selviasari; Muhammad Alfa Niam (Journal of Economy, Accounting and Management Science (JEAMS), 2023)
Indonesia as a developing country is actively involved in various development initiatives. To increase tax revenue, the government consistently strives to enact tax laws and policies that promote investment and business. Indonesia's economy has suffered due to the Covid-19 outbreak. Because this virus has had an effect on the economy, trade and business entities. The epidemic drastically reduced the turnover of every business entity. The rules for providing tax breaks to business owners who are required to pay Covid-19 taxes have been approved by the Minister of Finance. This research is a comparative non-statistical qualitative research that aims to compare income tax calculations. Data in this study was obtained through interviews and documentation. The results showed that there was a tax incentive in 2020 that eased the company in paying income tax in the April-December 2020 tax period. This tax incentive is issued by the government based on PMK No. 44/PMK.03/2020 where companies with revenues less than or equal to IDR 4.8 billion in income tax will be borne by the government as long as this regulation is enforced. PT Yureka Edukasi Cipta received an incentive of Rp2,503,800 and only paid PPH of Rp900,940 to the government. So that in 2020 the company received a net profit after tax of IDR 139,410,860. In 2020 the company received incentives, while in 2021 it did not get incentives because it had almost two times of revenue